Method for evaluating quality of positive electrode active material, positive electrode active material, and method for preparing positive electrode

CN119318034APending Publication Date: 2025-01-14LG CHEM LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046933.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-09-27
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The positive electrode active material used in lithium secondary batteries breaks due to particle separation during repeated charging and discharging, resulting in a decrease in battery characteristics. The ratio of NiO reduction layer increases when preparing the positive electrode active material in the form of a single particle, affecting battery performance.

Method used

By measuring the surface Raman spectrum of the positive electrode active material, the Raman displacement value of the peak corresponding to the Alg vibration mode of LiNiO2 and the peak intensity ratio of the Alg vibration mode of LiCoO2 are determined to screen high-quality positive electrode active materials and at high temperatures The heat treatment forms a cobalt-containing coating to control the formation of the NiO reduction layer.

Benefits of technology

Effectively screen out high-quality positive electrode active materials, improve the resistance performance of lithium secondary batteries, and reduce the resistance increase rate of the battery during repeated charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to: a method for evaluating the quality of a positive electrode active material, the method comprising: a step (A) of determining the positive electrode active material as a good product when a Raman shift value of a peak corresponding to an A1g vibration mode of LiNiO2 in a Raman spectrum of the surface of the positive electrode active material satisfies a preset positive electrode active material quality evaluation criterion; a positive electrode active material which is determined as a good product by the method and which can further improve the performance of the battery; and a method for preparing a positive electrode, the method comprising a step for evaluating the quality of the positive electrode active material by the method for evaluating the quality of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0122638, filed on September 27, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a method for evaluating the quality of a positive electrode active material, a positive electrode active material and a method for preparing a positive electrode. The method for preparing a positive electrode comprises the step of evaluating the quality of the positive electrode active material by the method for evaluating the quality of the positive electrode active material. Background Art

[0004] With the recent technological development and increase in demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources has significantly increased.

[0005] The positive electrode active material used in lithium secondary batteries is generally in the form of spherical secondary particles formed by the aggregation of hundreds of submicron-sized fine primary particles. However, the problem with the positive electrode active material in the form of secondary particles is that as the aggregated primary particles separate during repeated charging and discharging, the secondary particles break and the battery characteristics are reduced.

[0006] In order to solve this problem, positive electrode active materials in the form of single particles are being actively developed, but when preparing positive electrode active materials in the form of single particles, because it is necessary to sinter at a higher temperature than when preparing positive electrode active materials in the form of secondary particles, there is a problem of increasing the ratio of the NiO reduction layer on the particle surface. When the ratio of the NiO reduction layer on the surface of the positive electrode active material increases, problems such as increased battery resistance, reduced capacity, and reduced output occur, and therefore, it is necessary to control the NiO reduction layer.

[0007] In order to control the NiO reduction layer, in the case where the surface of the positive electrode active material is surface-treated with a cobalt-containing material, as the cobalt-containing material diffuses, the NiO reduction layer decreases and a cobalt-containing coating layer is formed.

[0008] Since the performance of the positive electrode active material varies with the degree of cobalt diffusion, there is a need not only for an evaluation method that more accurately confirms the degree of cobalt diffusion, but also for the development of a positive electrode active material that can further improve the performance of the battery. Summary of the invention

[0009] Technical issues

[0010] One aspect of the present invention provides: a method for evaluating the quality of a positive electrode active material, which can easily screen out poor-quality positive electrode active materials through Raman spectroscopy of the surface of the positive electrode active material; and a positive electrode active material, which is determined to be a good product by the method and can further improve the performance of a battery.

[0011] Another aspect of the present invention provides a method for preparing a positive electrode, the method comprising the step of evaluating the quality of a positive electrode active material by a method for evaluating the quality of a positive electrode active material.

[0012] Technical Solution

[0013] The present invention provides a method for evaluating the quality of a positive electrode active material, a positive electrode active material and a method for preparing a positive electrode.

[0014] (1) The present invention provides a method for evaluating the quality of a positive electrode active material, the method comprising: (A) a first determination step: when a Raman shift value of a peak corresponding to an Alg vibration mode of LiNiO2 in a Raman spectrum on the surface of the positive electrode active material satisfies a preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a good product, and when the Raman shift value does not satisfy the preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a defective product.

[0015] (2) The present invention provides the method for evaluating the quality of a positive electrode active material according to the above (1), wherein, before step (A), the method further comprises: step (A'): preparing a positive electrode active material in a single particle form, the positive electrode active material in a single particle form comprising: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating portion formed on the lithium transition metal oxide in a single particle form.

[0016] (3) The present invention provides the method for evaluating the quality of a positive electrode active material according to (2) above, wherein the positive electrode active material in the form of a single particle is prepared by heat-treating a mixture in which a single particle of a lithium transition metal oxide and a cobalt raw material are mixed.

[0017] (4) The present invention provides a method for evaluating the quality of a positive electrode active material according to any one of (1) to (3) above, wherein the pre-set positive electrode active material quality evaluation standard in step (A) is: the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 is 560 cm -1 above.

[0018] (5) The present invention provides a method for evaluating the quality of a positive electrode active material according to any one of (1) to (4) above, wherein the method further comprises: (B) a second determination step of: when the peak (550 cm-1) corresponding to the Alg vibration mode of LiCoO2 in the Raman spectrum of the surface of the positive electrode active material determined as a good product in step (A) is -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) was 0.3 or less, the positive electrode active material was determined to be a good product, and when the ratio was greater than 0.3, the positive electrode active material was determined to be a defective product.

[0019] (6) The present invention provides a method for preparing a positive electrode, the method for preparing a positive electrode comprising the following steps:

[0020] (S1) preparing a positive electrode active material in a single particle form, the positive electrode active material in a single particle form comprising: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating portion formed on the lithium transition metal oxide in a single particle form;

[0021] (S2) evaluating the quality of the positive electrode active material by the method of any one of (1) to (5) above; and

[0022] (S3) A positive electrode is prepared by using the positive electrode active material determined to be a good product.

[0023] (7) The present invention provides the method for producing a positive electrode according to (6) above, wherein the positive electrode active material in the form of a single particle is produced by heat-treating a mixture in which a lithium transition metal oxide in the form of a single particle and a cobalt raw material are mixed.

[0024] (8) The present invention provides the method for preparing a positive electrode according to (6) above, wherein a single-particle positive electrode active material is prepared by heat-treating a mixture in which a single-particle lithium transition metal oxide and a cobalt raw material are mixed at a temperature greater than 720°C and less than 780°C.

[0025] (9) The present invention provides a single-particle positive electrode active material, the single-particle positive electrode active material comprising: a single-particle lithium transition metal oxide; and a cobalt-containing coating portion formed on the single-particle lithium transition metal oxide,

[0026] The Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is 560 cm -1 above.

[0027] (10) The present invention provides the positive electrode active material in the form of a single particle according to (9) above, wherein the positive electrode active material in the form of a single particle further comprises island-shaped LiCoO 2 discontinuously formed on the surface.

[0028] (11) The present invention provides a single-particle positive electrode active material according to (9) or (10) above, wherein in the Raman spectrum of the surface of the positive electrode active material, a peak (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 )’s strength ratio is less than 0.3.

[0029] (12) The present invention provides a single-particle positive electrode active material according to any one of (9) to (11) above, wherein the single-particle positive electrode active material has an average particle size (D 50 ).

[0030] (13) The present invention provides a single-particle positive electrode active material according to any one of (9) to (12) above, wherein the single-particle positive electrode active material has a form in which 50 or less primary particles are aggregated, each of which is composed of 10 or less single crystal grains.

[0031] (14) The present invention provides a single particle form of a positive electrode active material according to any one of (9) to (13) above, wherein the single particle form of a lithium transition metal oxide is a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn).

[0032] (15) The present invention provides the positive electrode active material in the form of a single particle according to any one of (9) to (14) above, wherein the lithium transition metal oxide in the form of a single particle has a composition represented by Formula 1.

[0033] [Formula 1]

[0034] Li a Ni b Co c Mn d M 1 e O2

[0035] Among them, in formula 1,

[0036] M 1is at least one selected from the following: aluminum (Al), zirconium (Zr), boron (B), tungsten (W), molybdenum (Mo), chromium (Cr), niobium (Nb), magnesium (Mg), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), tin (Sn), yttrium (Y), zinc (Zn), fluorine (F), phosphorus (P), and sulfur (S), and

[0037] 0.9 ≤ a ≤ 1.1, 0.8 ≤ b < 1.0, 0 < c < 0.2, 0 < d < 0.2, 0 ≤ e ≤ 0.1 and b + c + d + e = 1.

[0038] (16) The present invention provides a positive electrode active material in a single particle form according to any one of (9) to (15) above, wherein the coating portion is a region from the surface of the positive electrode active material toward the center, 5 nm to 100 nm.

[0039] Beneficial Effects

[0040] The method for evaluating the quality of the positive electrode active material according to the present invention can easily determine a high-quality positive electrode active material by only measuring the Raman spectrum of the surface of the positive electrode active material.

[0041] The positive electrode active material according to the present invention can improve the resistance performance of a lithium secondary battery. Detailed Description

[0042] It should be understood that the words or terms used in this specification and the claims should not be construed as having the meanings defined in a common dictionary, and it should be further understood that the words or terms should be construed as having meanings consistent with their meanings in the context of the related technical field and technical concept of the present invention based on the principle that the present inventor can appropriately define the meanings of the said words or terms to best interpret the present invention.

[0043] It should be further understood that the terms "comprising", "including", or "having" in this specification specify the existence of the said features, numbers, steps, elements, or combinations thereof, but do not exclude the existence or addition of one or more other features, numbers, steps, elements, or combinations thereof.

[0044] The term "on" in this specification not only refers to the case where one component is directly formed on the upper surface of another component, but also includes the case where an intermediate component may exist.

[0045] In this specification, the expression "positive electrode active material in the form of a single particle" is a concept in contrast to the positive electrode active material in the form of spherical secondary particles formed by the aggregation of hundreds of primary particles prepared by conventional methods, wherein it refers to a positive electrode active material composed of 50 or less primary particles. Specifically, in the present invention, the positive electrode active material in the form of a single particle may be a single particle composed of one primary particle, or may be a secondary particle form in which 2 to 50, 2 to 40, 2 to 30, 2 to 20, 2 to 15, 2 to 10 or 2 to 5 primary particles are aggregated. In this case, the expression "primary particle" refers to the smallest particle unit identified when the positive electrode active material is observed by a scanning electron microscope.

[0046] The primary particle may be composed of 10 or less single crystal grains, and the grains may be analyzed using an electron backscatter diffraction (EBSD) analyzer. A single crystal grain is a unit represented by the same color in the electron backscatter diffraction (EBSD) Euler diagram data of one positive electrode active material particle, wherein it is a grain in which no grain boundary exists.

[0047] The average particle size (D 50 ) refers to the particle size at which 50% of the volume cumulative particle size distribution of the positive electrode active material precursor, the positive electrode active material or the lithium transition metal oxide powder is obtained. Average particle size (D 50 ) can be measured by using a laser diffraction method. For example, after the positive electrode active material powder is dispersed in a dispersion medium, the dispersion medium is introduced into a commercially available laser diffraction particle size measuring instrument (e.g., Microtrac MT 3000), and then irradiated with ultrasonic waves of about 28 kHz at an output of 60 W to obtain a volume cumulative particle size distribution diagram, and then the average particle size D can be measured by obtaining a particle size corresponding to 50% of the volume cumulative amount. 50 .

[0048] In this specification, the average grain size (D EBSD ) refers to the particle size of 50% in the volume cumulative particle size distribution of the single crystal grains obtained by using the EBSD analysis of a scanning electron microscope (SEM). EBSD analysis can utilize SEM-EBSD equipment (e.g., FEI Quanta 200-EDAX Velocity super OIM 8) to obtain images, and image analysis software (EDAX OIM Analysis) can be utilized to analyze images.

[0049] After placing the sample on a general X-ray diffraction (XRD) holder, pretreatment was performed so that the surface height of the sample was made uniform by compressing the sample with a glass slide, and the Raman spectrum in this specification was obtained by measuring a portion corresponding to an area of ​​410 μm×100 μm of the sample located on the XRD holder with a Raman spectrometer (using a 532 nm laser).

[0050] Hereinafter, the present invention will be described in more detail.

[0051] Method for evaluating the quality of positive electrode active materials

[0052] The method for evaluating the quality of a positive electrode active material according to the present invention is characterized in that the method comprises: (A) a first determination step: when the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material meets a preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a good product, and when the Raman shift value does not meet the preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a defective product.

[0053] Prior to step (A), the method for evaluating the quality of a positive electrode active material may include: step (A'): preparing a positive electrode active material in a single particle form, wherein the positive electrode active material in a single particle form comprises: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating formed on the lithium transition metal oxide in a single particle form. In addition, after step (A), the method for evaluating the quality of a positive electrode active material may further include: (B) a second determination step: when a peak (550 cm-1) corresponding to the Alg vibration mode of LiCoO2 in the Raman spectrum of the surface of the positive electrode active material determined as a good product in step (A) is -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) was 0.3 or less, the positive electrode active material was determined to be a good product, and when the ratio was greater than 0.3, the positive electrode active material was determined to be a defective product.

[0054] The method for evaluating the quality of the positive electrode active material according to the present invention can easily determine the high-quality positive electrode active material by measuring only the Raman spectrum of the surface of the positive electrode active material. Specifically, the method for evaluating the quality of the positive electrode active material according to the present invention can easily confirm the positive electrode active material that can improve the resistance characteristics of the battery when the positive electrode active material is used in a lithium secondary battery.

[0055] Hereinafter, each step of the method for evaluating the quality of a positive electrode active material according to the present invention will be described in more detail.

[0056] Step (A')

[0057] Step (A') is a step of preparing a single-particle positive electrode active material before step (A), wherein the single-particle positive electrode active material comprises: a single-particle lithium transition metal oxide; and a cobalt-containing coating portion formed on the single-particle lithium transition metal oxide.

[0058] According to the present invention, a single-particle positive electrode active material can be prepared by heat-treating a mixture in which a single-particle lithium transition metal oxide and a cobalt raw material are mixed. When the mixture is heat-treated, while cobalt ions present in the cobalt raw material diffuse from the surface of the single-particle lithium transition metal oxide to the center, a Raman shift of a peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is confirmed.

[0059] The heat treatment temperature may be in the range of greater than 720°C and less than 780°C, and specifically may be greater than 720°C, greater than 730°C, greater than 740°C, less than 760°C, less than 770°C, and less than 780°C. When the mixture is heat treated within the above temperature range, the resistance performance of a lithium secondary battery containing a positive electrode containing a positive electrode active material may be excellent because the cobalt-containing coating is optimally formed on the surface of the positive electrode active material in the form of a single particle. Specifically, when the mixture is heat treated within the above temperature range, a positive electrode active material in the form of a single particle may be prepared, the positive electrode active material in the form of a single particle comprising: a lithium transition metal oxide in the form of a single particle; and a cobalt-containing coating formed on the lithium transition metal oxide in the form of a single particle, wherein the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is 560 cm -1 The above. LiNiO2, which is the main component of the lithium transition metal oxide in the form of a single particle, and LiCoO2 confirmed in the coating portion have the same crystal structure (R3m), and the R3m crystal structure has two types of vibration modes, A1g and Eg, in the Raman spectrum, wherein, when the mixture is heat-treated within the above temperature range, while cobalt is infiltrated into the positive electrode active material, an appropriate amount of cobalt (Co) is infiltrated into the LiNiO2 lattice, and as a result, the frequency of the LiNiO2 vibration mode increases. In addition, the positive electrode active material prepared by heat-treating the mixture within the above temperature range has a peak (550 cm-1) corresponding to the A1g vibration mode of LiCoO2 in the Raman spectrum of the surface. -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm-1 ) can be 0.3 or less. The reason is that when the mixture is heat treated in the above temperature range, while cobalt infiltrates into the positive electrode active material, the surface LiCoO2 is reduced. In addition, when cobalt infiltrates into the positive electrode active material, the resistance of the battery may be reduced because the NiO present on the surface is reduced and the surface is stabilized.

[0060] In the present invention, the coating portion is a layer formed by diffusion of cobalt from the surface of the lithium transition metal oxide in the form of a single particle in the direction toward the center when the lithium transition metal oxide in the form of a single particle is mixed with a cobalt raw material and then heat treated. Thus, the composition of the coating portion is similar to the composition of the lithium transition metal oxide in the form of a single particle contained in the positive electrode active material of the present invention, but the ratio of cobalt in all metals other than lithium is greater than the ratio of cobalt in all metals other than lithium in the lithium transition metal oxide in the form of a single particle. While cobalt diffuses from the surface of the lithium transition metal oxide in the form of a single particle in the direction toward the center, the nickel (Ni) present in the lithium transition metal oxide in the form of a single particle can be replaced by Co, and the coating portion can have the same structure as the lithium transition metal oxide in the form of a single particle, that is, a layered structure.

[0061] In the present invention, the coating portion may be a region of 5 nm to 100 nm from the surface of the positive electrode active material toward the center. Specifically, the coating portion may be a region of 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, or 100 nm from the surface of the positive electrode active material toward the center.

[0062] Step (A)

[0063] Step (A) is a first determination step: when the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material meets the pre-set positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a good product, and when the Raman shift value does not meet the pre-set positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a defective product.

[0064] When the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material meets the pre-set positive electrode active material quality evaluation standard, the resistance performance of the lithium secondary battery containing the positive electrode containing the positive electrode active material can be significantly improved. Specifically, with repeated charge and discharge cycles at high temperature, the lithium secondary battery can have a small resistance increase rate value.

[0065] According to the present invention, the pre-set positive electrode active material quality evaluation standard in step (A) can be: the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 is 560 cm -1 Specifically, the pre-set positive electrode active material quality evaluation standard may be: the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 is 560 cm -1 Over 570 cm -1 Below, 580 cm -1 Below, 590 cm -1 Below, and less than 597 cm -1 In this case, it can be considered that the cobalt-containing coating portion is formed on the surface of the positive electrode active material in the form of a single particle to optimize for improving the resistance performance of the lithium secondary battery.

[0066] Step (B)

[0067] Step (B) is a step of: when a peak (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) is less than 0.3, the positive electrode active material is determined to be a good product. Specifically, the peak corresponding to the Alg vibration mode of LiCoO2 (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) can be greater than 0, greater than 0.10, and less than 0.30.

[0068] In the Raman spectrum of the surface of the positive electrode active material, a peak corresponding to the Alg vibration mode of LiCoO2 (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) is below 0.30, because an appropriate amount of electrochemically active LiCoO2 crystal structure is formed on the surface instead of electrochemically inert NiO, the resistance is reduced.

[0069] Positive electrode active material

[0070] The present invention provides a single-particle positive electrode active material, the single-particle positive electrode active material comprising: a single-particle lithium transition metal oxide; and a cobalt-containing coating formed on the single-particle lithium transition metal oxide, wherein the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is 560 cm -1 The Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 can be specifically 560 cm -1 Over 570 cm -1 Below, 580 cm -1 Below, 590 cm -1 Below, and less than 597 cm -1 .

[0071] The positive electrode active material according to the present invention is a positive electrode active material determined to be good by the method for evaluating the quality of a positive electrode active material according to the present invention.

[0072] The inventors of the present invention have confirmed that a positive electrode active material in the form of a single particle comprises: a lithium transition metal oxide in the form of a single particle; and a cobalt-containing coating formed on the lithium transition metal oxide in the form of a single particle, wherein the Raman shift value of a peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is 560 cm -1 In the above case, the resistance performance of the lithium secondary battery including the positive electrode active material is improved.

[0073] The cathode active material according to the present invention is the same as the cathode active material of step (A'), wherein it can be prepared as described above.

[0074] The Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is less than 560 cm -1 In the case of , since cobalt is not diffused much into the surface portion of the positive electrode active material, there is a problem that the surface is destabilized and the resistance performance of the lithium secondary battery including the positive electrode active material is not improved.

[0075] According to the present invention, the positive electrode active material in the form of a single particle may further include island-shaped LiCoO2 discontinuously formed on the surface. The island-shaped LiCoO2 is discontinuously formed on the surface of the positive electrode active material. That is, the island-shaped LiCoO2 does not completely cover the surface of the positive electrode active material, but is partially dispersed and distributed. Based on the total area of ​​the surface of the positive electrode active material, the island-shaped LiCoO2 may be discontinuously formed on an area of ​​5% to 50%. In this case, because the coating portion and the island-shaped LiCoO2 exist in an appropriate ratio, the performance of the battery can be further improved.

[0076] According to the present invention, the peak (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) can be less than 0.3. Specifically, the peak corresponding to the Alg vibration mode of LiCoO2 (550 cm -1 Up to 620cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) can be greater than 0, greater than 0.10, and less than 0.30. In this case, since an appropriate amount of electrochemically active LiCoO2 crystal structure is present on the surface of the positive electrode active material instead of electrochemically inert NiO, the resistance performance of the lithium secondary battery containing the positive electrode active material can be further improved. The peak corresponding to the Alg vibration mode of LiCoO2 (550 cm -1 Up to 620 cm -1 ) may be the peak caused by island-like LiCoO2.

[0077] According to the present invention, the positive electrode active material in the form of a single particle may have an average particle size (D 50 Specifically, the positive electrode active material in the form of a single particle may have an average particle size (D) of 0.1 μm, 1.0 μm, 2.0 μm or more, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm or 10.0 μm or less. 50 ). In this case, since the rolling ratio of the battery including the positive electrode active material in the form of a single particle can be increased, the performance of the battery can be further improved.

[0078] According to the present invention, the positive electrode active material in the form of a single particle may have a form in which 50 or less, specifically 30, 20, 10 or 5 or less primary particles are aggregated, each of which is composed of 10 or less single crystal grains. In this case, the capacity and resistance performance of the battery can be improved, and the occurrence of cracks in the particles during repeated charging and discharging can be reduced. In this case, the single crystal grains may have an average particle size (D EBSD). Specifically, the single crystal grains may have an average particle size (D of 0.1 μm, 1.0 μm, 2.0 μm or more, and 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm or 10.0 μm or less EBSD ).

[0079] According to the present invention, the lithium transition metal oxide in the form of single particles may be a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn). In this case, the lithium transition metal oxide in the form of single particles may contain 80 mol% or 85 mol% or more of nickel (Ni) among all metals other than lithium. Specifically, the lithium transition metal oxide in the form of single particles may specifically have a composition represented by the following formula 1.

[0080] [Formula 1]

[0081] Li a Ni b Co c Mn d M 1 e O2

[0082] In Formula 1,

[0083] M 1 is at least one selected from the following: aluminum (Al), zirconium (Zr), boron (B), tungsten (W), molybdenum (Mo), chromium (Cr), niobium (Nb), magnesium (Mg), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), cerium (Ce), tin (Sn), yttrium (Y), zinc (Zn), fluorine (F), phosphorus (P), and sulfur (S), and

[0084] 0.9 ≤ a ≤ 1.1, 0.8 ≤ b < 1.0, 0 < c < 0.2, 0 < d < 0.2, 0 ≤ e ≤ 0.1 and b + c + d + e = 1.

[0085] b represents the atomic fraction of nickel among the metal elements other than lithium in the lithium transition metal oxide, where b may be 0.8, 0.85 or more, and 0.95 or 0.98 or less.

[0086] c represents the atomic fraction of cobalt among the metal elements other than lithium in the lithium transition metal oxide, where c may be 0.01 or more, and 0.1 or 0.2 or less.

[0087] d represents the atomic fraction of manganese among the metal elements other than lithium in the lithium transition metal oxide, where d may be 0.01 or more, and 0.1 or 0.2 or less.

[0088] e represents the element M among the metal elements other than lithium in the lithium transition metal oxide1 The atomic fraction of , wherein e can be greater than 0 and less than 0.02, 0.05 or 0.1.

[0089] In the present invention, the coating portion is a layer formed by diffusion of cobalt from the surface of the lithium transition metal oxide in the form of a single particle in a direction toward the center when the lithium transition metal oxide in the form of a single particle is mixed with a cobalt raw material and then heat treated. Thus, the composition of the coating portion is similar to the composition of the lithium transition metal oxide in the form of a single particle contained in the positive electrode active material of the present invention, but the ratio of cobalt in all metals other than lithium is greater than the ratio of cobalt in all metals other than lithium in the lithium transition metal oxide in the form of a single particle. While cobalt diffuses from the surface of the lithium transition metal oxide in the form of a single particle in a direction toward the center, Ni present in the lithium transition metal oxide in the form of a single particle can be replaced by Co, and the coating portion can have the same structure as the lithium transition metal oxide in the form of a single particle, that is, a layered structure.

[0090] According to the present invention, the coating portion may be a region ranging from 5 nm to 100 nm from the surface of the positive electrode active material toward the center. The coating portion may specifically be a region ranging from 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm from the surface of the positive electrode active material toward the center.

[0091] In this specification, the coating portion is the area from the surface of the positive electrode active material to the point where the Co content measured by the transmission electron microscope (TEM)-energy dispersive X-ray spectroscopy (EDX) experiment is 1.1 times the total average Co content (mol %) of the positive electrode active material. In this case, in the TEM-EDX experiment, after a film sample with a thickness of 100 nm to 200 nm is made from the positive electrode active material powder using FEI's Helios G4 UX FIB equipment, the X-ray spectrum of the elements at each position of the sample is measured using FEI's Titan G280-200 ChemiSTEM equipment and EDX (column super X-energy dispersive X-ray spectrum) device (ChemiSTEM technology), and the molar ratio (mol %) value of each element can be obtained by comparing the intensity.

[0092] Method for preparing positive electrode

[0093] The method for preparing a positive electrode according to the present invention is characterized in that the method for preparing a positive electrode comprises the following steps:

[0094] (S1) preparing a positive electrode active material in a single particle form, the positive electrode active material in a single particle form comprising: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating portion formed on the lithium transition metal oxide in the single particle form;

[0095] (S2) evaluating the quality of the positive electrode active material by the method for evaluating the quality of the positive electrode active material according to the present invention; and

[0096] (S3) A positive electrode is prepared by using the positive electrode active material determined to be a good product.

[0097] Hereinafter, each step of the method for preparing the positive electrode will be described in more detail.

[0098] Step (S1)

[0099] Step (S1) is a step of preparing a single-particle positive electrode active material, the single-particle positive electrode active material comprising: a single-particle lithium transition metal oxide; and a cobalt-containing coating portion formed on the single-particle lithium transition metal oxide.

[0100] The step (S1) is the same as the step (A') of the method for evaluating the quality of the positive electrode active material.

[0101] According to the present invention, a single-particle positive electrode active material can be prepared by heat-treating a mixture in which a single-particle lithium transition metal oxide and a cobalt raw material are mixed. When the mixture is heat-treated, while cobalt ions present in the cobalt raw material diffuse from the surface of the single-particle lithium transition metal oxide to the center, a Raman shift of a peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is confirmed.

[0102] The heat treatment temperature may be in the range of greater than 720°C and less than 780°C, and specifically may be greater than 720°C, greater than 730°C, greater than 740°C, less than 760°C, less than 770°C, and less than 780°C. When the mixture is heat treated within the above temperature range, since the cobalt-containing coating is optimally formed on the surface of the positive electrode active material in the form of a single particle, the resistance performance of a lithium secondary battery containing a positive electrode containing the positive electrode active material may be improved. Specifically, when the mixture is heat treated within the above temperature range, a positive electrode active material in the form of a single particle may be prepared, the positive electrode active material in the form of a single particle comprising: a lithium transition metal oxide in the form of a single particle; and a cobalt-containing coating formed on the lithium transition metal oxide in the form of a single particle, wherein the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is 560 cm -1In addition, the positive electrode active material prepared by heat treating the mixture within the above temperature range has a peak (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 )'s strength ratio can be less than 0.3.

[0103] Step (S2)

[0104] Step (S2) is a step of evaluating the quality of the positive electrode active material by the method for evaluating the quality of the positive electrode active material according to the present invention.

[0105] That is, for a positive electrode active material in the form of a single particle in which a cobalt-containing coating is formed, a Raman spectrum of the surface of the positive electrode active material is obtained by using a Raman spectrometer, and step (S2) includes the following steps: when the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material meets the preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a good product, and when the Raman shift value does not meet the preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a defective product.

[0106] The specific details are as described above.

[0107] Step (S3)

[0108] Step (S3) is a step of preparing a positive electrode by using the positive electrode active material determined to be a good product.

[0109] The positive electrode can be prepared by applying a positive electrode active material layer-forming composition (slurry) containing a positive electrode active material determined to be a good product, a conductive material, and a binder onto a current collector and then drying it to form an active material layer. The active material layer can be formed on one surface or both surfaces of the current collector.

[0110] There is no particular limitation on the current collector as long as it is conductive and does not cause adverse chemical changes in the battery. For the positive electrode current collector, for example, stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. For the negative electrode current collector, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.; and aluminum-cadmium alloys can be used.

[0111] The current collector can generally have a thickness of 3 μm to 500 μm, and fine unevenness can be formed on the surface of the current collector to improve the adhesion of the positive electrode material or the negative electrode material. For example, the current collector can be used in various shapes such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.

[0112] The composition for forming the positive electrode active material layer can be prepared by dissolving or dispersing the positive electrode active material, conductive material, and binder determined to be of good quality in a solvent.

[0113] The positive electrode active material determined to be of good quality is a compound capable of reversibly intercalating and deintercalating lithium. Specifically, the positive electrode active material can be a lithium composite metal oxide containing lithium and at least one transition metal such as cobalt, manganese, nickel, or aluminum. More specifically, the lithium composite metal oxide can include: lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1- Y Mn Y O2 (0 < Y < 1), LiMn 2-Z Ni Z O4 (0 < Z < 2)), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (0 < Y1 < 1)), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (0 < Z1 < 2), etc.), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p Co q Mn r1 )O2 (0 < p < 1, 0 < q < 1, 0 < r1 < 1 and p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2 and p1 + q1 + r2 = 2)) or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M S2)O2 (where M is selected from: aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), and molybdenum (Mo), and p2, q2, r3, and S2 are atomic fractions of respective independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1 and p2 + q2 + r3 + S2 = 1), etc.), and may include any one of them or a mixture of two or more thereof.

[0114] Based on the total weight of the active material layer, the content of the positive electrode active material determined to be a good product can be 80% to 99% by weight, more specifically 85% to 98% by weight. When the amount of the positive electrode active material determined to be a good product is within the above range, excellent capacity characteristics and electrochemical performance can be obtained.

[0115] The conductive material is used to provide conductivity to the electrode. Among them, any conductive material can be used without particular limitation as long as it has appropriate electron conductivity and does not cause adverse chemical changes in the battery. Specific examples of the conductive material can be: graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, and carbon fiber; powders or fibers of metals such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxides; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used.

[0116] Based on the total weight of the active material layer, the content of the conductive material can be 1% to 30% by weight.

[0117] The binder improves the adhesion between the active material particles and the adhesion between the active material and the current collector. Specific examples of the binder can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride - hexafluoropropylene copolymer (PVDF - co - HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene - propylene - diene monomer (EPDM), sulfonated EPDM, styrene - butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one of them or a mixture of two or more thereof can be used.

[0118] Based on the total weight of the positive electrode active material layer, the content of the binder can be 1% to 30% by weight.

[0119] The solvent may be a commonly used solvent in the art, and may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one thereof or a mixture of two or more thereof may be used. If the coating thickness, preparation yield or operability of the positive electrode active material layer forming composition are taken into consideration, the positive electrode active material layer forming composition may be adjusted to have a suitable viscosity, then the amount of the solvent may be sufficient, and is not particularly limited.

[0120] As described above, the positive electrode can be prepared from the positive electrode active material determined as a good product according to the method for evaluating the quality of the positive electrode active material of the present invention, and the positive electrode can be used as an electrode of a lithium secondary battery. Because the lithium secondary battery has improved resistance properties, the lithium secondary battery can be applied to: portable devices such as mobile phones, laptops and digital cameras; and electric vehicles such as hybrid electric vehicles (HEV).

[0121] Preferred Embodiments

[0122] Hereinafter, examples of the present invention will be described in detail in a manner that a person skilled in the art can easily implement the present invention. However, the present invention can be embodied in many different forms and should not be construed as being limited to the examples set forth herein.

[0123] Preparation Example 1

[0124] By combining the 0.88 Co 0.03 Mn 0.09 A single particle-form lithium transition metal oxide of a composition represented by O2 was mixed with powdered Co(OH)2 (Huayou Cobalt Co., Ltd.) at a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 660°C in an oxygen atmosphere for 3 hours to prepare a single particle-form positive electrode active material (average particle size: 4 μm) in which a cobalt-containing coating was formed.

[0125] Preparation Example 2

[0126] A positive electrode active material in the form of a single particle (average particle diameter: 4 μm) having a cobalt-containing coating layer formed therein was prepared in the same manner as in Preparation Example 1 except that the mixture was heat-treated at a temperature of 680° C.

[0127] Preparation Example 3

[0128] A positive electrode active material in the form of a single particle (average particle diameter: 4 μm) having a cobalt-containing coating layer formed therein was prepared in the same manner as in Preparation Example 1 except that the mixture was heat-treated at a temperature of 700° C.

[0129] Preparation Example 4

[0130] A positive electrode active material in the form of a single particle (average particle diameter: 4 μm) having a cobalt-containing coating layer formed therein was prepared in the same manner as in Preparation Example 1 except that the mixture was heat-treated at a temperature of 720° C.

[0131] Preparation Example 5

[0132] A positive electrode active material in the form of a single particle (average particle diameter: 4 μm) having a cobalt-containing coating layer formed therein was prepared in the same manner as in Preparation Example 1 except that the mixture was heat-treated at a temperature of 740° C.

[0133] Preparation Example 6

[0134] A positive electrode active material in the form of a single particle (average particle diameter: 4 μm) having a cobalt-containing coating layer formed therein was prepared in the same manner as in Preparation Example 1 except that the mixture was heat-treated at a temperature of 760° C.

[0135] Preparation Example 7

[0136] A positive electrode active material in the form of a single particle (average particle diameter: 4 μm) having a cobalt-containing coating layer formed therein was prepared in the same manner as in Preparation Example 1 except that the mixture was heat-treated at a temperature of 780° C.

[0137] Example: Quality evaluation of positive electrode active materials

[0138] After placing samples of each positive electrode active material prepared in Preparation Examples 1 to 7 on a general X-ray diffraction (XRD) holder, pretreatment was performed so that the surface height of the sample was made uniform by compressing the sample with a glass slide, and the Raman spectrum of the surface of the positive electrode active material was obtained by measuring a portion corresponding to an area of ​​410 μm×100 μm of the sample located on the XRD holder using a Raman spectrometer (using a 532 nm laser).

[0139] The Raman shift value of the peak corresponding to the A1g vibration mode of LiNiO2 and the peak corresponding to the A1g vibration mode of LiCoO2 (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) and the results are shown in Table 1 below.

[0140]

[0141] Referring to Table 1, the positive active materials of Preparation Examples 5 and 6 were determined to be good products, which corresponds to the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum being 560 cm -1 The above (preset value).

[0142] The positive active materials of Preparation Examples 1 to 4 and Preparation Example 7 were all determined to be defective because the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum did not meet the 560 cm -1 above.

[0143] In addition, for the positive electrode active materials of Preparation Examples 5 and 6, it can be confirmed that the peak corresponding to the Alg vibration mode of LiCoO2 in the Raman spectrum (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 )’s strength ratio LiNiO2 / LiCoO2 is less than 0.3.

[0144] Experimental example: Battery characteristics evaluation

[0145] (Half-cell preparation)

[0146] A composition for forming a positive electrode active material layer was prepared by adding each positive electrode active material prepared in Preparation Examples 1 to 7, a carbon black conductive material (Denka Company Limited, Denka Black) and a PVdF binder (Kureha Corporation, KF1300) in a weight ratio of 95:3:2 to an N-methylpyrrolidone (NMP) solvent (Daejung Chemicals & Metals, Co., Ltd.).

[0147] The positive electrode active material layer was formed by coating the positive electrode active material layer-forming composition on one surface of a 20 μm thick aluminum foil current collector and drying the coated current collector at a temperature of 135° C. for 3 hours. Subsequently, the positive electrode active material layer was rolled by a rolling method so that the porosity of the positive electrode active material layer after rolling was 20 volume % to prepare a positive electrode.

[0148] A half-cell is prepared by using metallic lithium as the negative electrode and a positive electrode.

[0149] (Evaluation of battery cycle characteristics)

[0150] Each of the half-cells prepared above was charged to 4.25 V at a constant current (CC) of 0.2 C at 25°C, and then charged at a constant voltage (CV) of 4.25 V until the charging current was 0.05 mAh (cut-off current), and then each half-cell was left to stand for 20 minutes and then discharged to 2.5 V at a constant current of 0.2 C.

[0151] Thereafter, the battery was transferred to a chamber at 45° C., and the battery was charged to 4.25 V at a constant current of 0.33 C, the battery was charged at a constant voltage (CV) of 4.25 V until the charging current was 0.05 mAh (cut-off current), and the battery was discharged to 2.5 V at a constant current of 0.33 C as one cycle, and 50 charge and discharge cycles were performed. In this case, too, the percentage of the direct current internal resistance (DCIR) value in the 50th cycle relative to the DCIR value in the 1st cycle was set as the resistance increase rate, and the resistance increase rate is shown in the following Table 2. For reference, the DCIR value in the nth cycle is a value calculated by dividing the difference between the voltage 10 seconds after the start of discharge and the voltage in the fully charged state, which is obtained when the battery is discharged to 2.5 V at a constant current of 0.33 C, by the current in the nth cycle.

[0152]

[0153] As shown in Table 2, for the positive electrode active materials of Preparation Examples 5 and 6 classified as good products according to the method for evaluating the quality of a positive electrode active material of the present invention, the resistance increase rate of the battery containing the positive electrode active material was 140.0% or less, wherein it can be confirmed that the resistance increase rate is significantly lower than the resistance increase rate of the battery containing the positive electrode active materials of Preparation Examples 1 to 4 and 7.

[0154] Therefore, according to the present invention, it can be understood that by measuring the Raman spectrum of the surface of the positive electrode active material, the positive electrode active material of poor quality can be easily screened out. That is, it can be understood that it is easier to select a good positive electrode active material that can improve the resistance performance of the lithium secondary battery. In addition, it can be understood that the positive electrode active material according to the present invention can improve the resistance performance of the lithium secondary battery.

Claims

1. A method for evaluating the quality of a positive electrode active material, the method comprising: (A) First determination step: When the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material meets the preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a good product, and When the Raman shift value does not meet the preset positive electrode active material quality evaluation standard, the positive electrode active material is determined to be a defective product.

2. The method according to claim 1, before step (A), further comprising: Step (A'): preparing a positive electrode active material in a single particle form, the positive electrode active material in a single particle form comprising: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating portion formed on the lithium transition metal oxide in a single particle form.

3. The method according to claim 2, wherein: The positive electrode active material in the form of a single particle is prepared by heat-treating a mixture in which the lithium transition metal oxide in the form of a single particle and a cobalt raw material are mixed.

4. The method according to claim 1, wherein: The pre-set positive electrode active material quality evaluation standard in step (A) is: the Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 is 560 cm -1 above.

5. The method according to claim 1, further comprising: (B) Second determination step: When the peak (550 cm-1) corresponding to the Alg vibration mode of LiCoO2 in the Raman spectrum of the surface of the positive electrode active material determined as the good product in the step (A) is -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 ) is less than 0.3, the positive electrode active material is determined to be a good product, and When the ratio is greater than 0.3, the positive electrode active material is determined to be a defective product.

6. A method for preparing a positive electrode, the method comprising the following steps: (S1) preparing a positive electrode active material in a single particle form, the positive electrode active material in a single particle form comprising: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating portion formed on the lithium transition metal oxide in a single particle form; (S2) evaluating the quality of the positive electrode active material by the method according to any one of claims 1 to 5; and (S3) A positive electrode is prepared by using the positive electrode active material determined to be a good product.

7. The method according to claim 6, wherein: The positive electrode active material in the form of a single particle is prepared by heat-treating a mixture in which the lithium transition metal oxide in the form of a single particle and a cobalt raw material are mixed.

8. The method according to claim 6, wherein: The positive electrode active material in the form of a single particle is prepared by heat-treating a mixture in which the lithium transition metal oxide in the form of a single particle and a cobalt raw material are mixed at a temperature greater than 720° C. and less than 780° C.

9. A positive electrode active material in a single particle form, the positive electrode active material comprising: a lithium transition metal oxide in a single particle form; and a cobalt-containing coating portion formed on the lithium transition metal oxide in the single particle form, in, The Raman shift value of the peak corresponding to the Alg vibration mode of LiNiO2 in the Raman spectrum of the surface of the positive electrode active material is 560 cm -1 above. 10 . The positive electrode active material in the form of a single particle according to claim 9 , further comprising island-shaped LiCoO 2 discontinuously formed on the surface.

11. The positive electrode active material in single particle form according to claim 9, wherein In the Raman spectrum of the surface of the positive electrode active material, the peak corresponding to the Alg vibration mode of LiCoO2 (550 cm -1 Up to 620 cm -1 ) is similar to the peak corresponding to the A1g vibration mode of LiNiO2 (500 cm -1 Up to 600 cm -1 )’s strength ratio is less than 0.

3.

12. The positive electrode active material in single particle form according to claim 9, wherein The positive electrode active material in the form of single particles has an average particle size (D 50 ).

13. The positive electrode active material in single particle form according to claim 9, wherein The positive electrode active material in the form of a single particle has a form in which 50 or less primary particles are aggregated, each of the primary particles being composed of 10 or less single crystal grains.

14. The positive electrode active material in single particle form according to claim 9, wherein The lithium transition metal oxide in the form of single particles is a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn).

15. The positive electrode active material in single particle form according to claim 9, wherein The lithium transition metal oxide in the form of a single particle has a composition represented by Formula 1: [Formula 1] Li a Ni b Co c Mr d M 1 e O2 Among them, in formula 1, M 1 is at least one selected from the group consisting of Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S, and 0.9 ≤ a ≤ 1.1, 0.8 ≤ b < 1.0, 0 < c < 0.2, 0 < d < 0.2, 0 ≤ e ≤ 0.1 and b + c + d + e = 1.

16. The positive electrode active material in single particle form according to claim 9, wherein The coating part is a region from the surface of the positive electrode active material towards the center with a thickness of 5 nm to 100 nm.

Citation Information

Patent Citations

  • Closed-loop, pressurized and sterile, controlled microenvironment cultivation

    KR1020220122638A